Suplementação da dieta de novilhos de três grupos genéticos em pastagem de Brachiaria brizantha cv. Marandu - Freitas, Djalma De; Fregadolli, Fábio Luiz; Bertipaglia, Liandra Maria Abaker; Melo, Gabriel Mauricio Peruca De; Reis, Ricardo Andrade [UNESP]; Berchielli, Telma Teresinha [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2011)
This trial was carried out to study the effects of supplementation level on performance of steers from different genetic groups (Nellore x Red Angus (NR), Nellore (NL) and Holstein crossbred (MH), and three experimental periods. The performance data for first period were analyzed according to randomized block (RB) design, with 3 treatments ((NR, NL and MH)) and 3 blocks. In second period, the RB design used with 3 x 3 factorial design, and 3 blocks. Factor A determined the group (NL and MH) and factor B the supplementation levels (0.2, 0.6 and 1% LW). In third period, the data were evaluated according to completely randomized design, with 2 x 3 factorial design. Factor A determined the group and factor B, three levels of supplementation. In the first, higher weight gain (p < 0.05) was observed for NR (0.79 kg day-1) compared to MH and NL (0.73 and 0.61 kg day-1). The concentrate intake varied for N. NR showed higher (p < 0.05) WG (0.91 kg day-1) compared to NL (0.75 kg day-1) and MH (0.76 kg day-1). The levels of supplements influenced (p < 0.05) WG (0.68, 0.81 and 0.92 referring to levels of 0.2, 0.6 and 1.0% LW). In third period, MH presented greater WG < 0.05) (0.895 kg day-1). No difference was verified on animals with 0.8 and 1.2% LW, with WG of 0.92 and 0.82 kg day-1.

Avaliou-se o efeito de níveis de suplementação no desempenho de novilhos de três grupos genéticos (Nelore x Red Angus (NR), Nelore (NL) e mestiço Holandês (MH)), em três períodos experimentais. O desempenho do primeiro período foi analisado em DBC, composto por três tratamentos (NR, NL e MH) e três blocos. No segundo período, usou-se DBC em esquema de análise fatorial 3 x 3, com três blocos. O fator A determinou o grupo (NR, NL e MH) e o fator B, níveis de suplementação (0,2; 0,6 e 1% PV). No terceiro período, usou-se DIC em esquema de análise fatorial 2 x 3. O fator A determinou o grupo (NL e MH) e o fator B, três níveis de suplementação. No início, foi verificado maior ganho de peso (GP) no NR (0,79 kg dia-1) comparado ao MH e N (0,73 e 0,61 kg dia-1). O consumo de concentrado variou no NL. No segundo período, o NR apresentou maior GP (0,91 kg dia-1) comparado ao NL (0,75 kg dia-1) e MH (0,76 kg dia-1), sendo influenciados pelos níveis de suplementação. No terceiro período, MH apresentou maior GP (0,89 kg dia-1). Não houve diferença entre os animais com 0,8 e 1,2% do PV, com GP de 0,82 e 0,92 kg dia-1.
Supplementation of the diets of three genetic groups of crossbred steers on Brachiaria brizantha cv. Marandu pasture
Keywords: mestiço Holandês; Nelore; níveis de concentrado; Red Angus; Holstein crossbred; Nelore; concentrate levels; Red Angus